NILAI EKONOMI TOTAL HUTAN KOTA PT. HOLCIM INDONESIA TBK DI KABUPATEN CILACAP, JAWA TENGAH - Raden Mohamad Mulyadin; Surati Surati (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2018)
High urban activities tend to impact on the degradation of environmental quality. One of the causes of environmental degradation is conversion of forests into office buildings and settlements. An effort to reduce enviromental quality degradation is by applying green open space (RTH) in which for the urban areas the most appropriate form is city's urban forest. City's urban forest in addition to having ecological values it has economic values. This study aims to determine total economic value of urban forest of PT. Holcim Indonesia Tbk in Cilacap Regency, Central Java. The study was carried out related to public perception, if the product or services produced by urban forest is calculated in term of monetary value such that, it is expected that the society would increasingly recognize the important role of urban forest. Measurements were carried out in 2013, using total economic value approach, covering direct and indirect values. The results showed that total economic value of urban forests of PT. Holcim Indonesia is IDR598,719,138,213.00 per year, consisting of direct benefit of IDR346,769,705,800.00 and indirect benefit of IDR251,949,432,413.00. The result of analysis shows that urban forest meets the feasibility requirement when viewed from the benefits obtained compared with cost incurred.